2013
DOI: 10.1371/journal.pone.0064744
|View full text |Cite
|
Sign up to set email alerts
|

Population Structure of Atlantic Mackerel (Scomber scombrus)

Abstract: Atlantic mackerel (Scomber scombrus) occurs on both sides of the north Atlantic and has traditionally been grouped into 5 spawning components, some of which were thought to be isolated natal homing stocks. Previous studies have provided no evidence for cross Atlantic migration and no or weak support for isolated spawning components within either side of the North Atlantic. We question the de-facto accepted hypothesis of isolation between spawning components on the basis of spawning and age distribution data. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
37
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 52 publications
(39 citation statements)
references
References 37 publications
2
37
0
Order By: Relevance
“…This simplistic population model has recently been challenged by results, indicating structures within the spawning components and substantial straying among the spawning components (Jansen and Gislason, 2013). A more complex population model is, therefore, needed to represent actual details and dynamics.…”
Section: Nursery Areas and Recruitment Variation Of Northeast Atlantimentioning
confidence: 99%
See 1 more Smart Citation
“…This simplistic population model has recently been challenged by results, indicating structures within the spawning components and substantial straying among the spawning components (Jansen and Gislason, 2013). A more complex population model is, therefore, needed to represent actual details and dynamics.…”
Section: Nursery Areas and Recruitment Variation Of Northeast Atlantimentioning
confidence: 99%
“…The elongate band of high density that runs parallel with the shelf edge was, to some extent, segmented by two areas of relatively low density, namely west of the English Channel (49.58N 88W) and around the Fair Isle Channel (608N 2.58W) (Figure 8). The Fair Isle Channel is also known to form a discontinuity in the spawning area and has been regarded as the border between the western and North Sea spawning components (Jansen and Gislason, 2013). However, the area west of the English Channel (49.58N) is in the middle of the spawning area for the western component, and a study that suggested spatial segregation within the western area did not indicate an abrupt shift around 49.58N .…”
Section: Nursery Areas and Recruitment Variation Of Northeast Atlantimentioning
confidence: 99%
“…However, from that year on (based on tagging experiments, which validated the migratory route of mackerel in the Northeast Atlantic waters), it was agreed to unify the population in a single stock. This stock is divided into three spawning components (ICES, 1996): North Sea Spawning Component (NSC), Western Spawning Component (WSC, Biscay to northwest of Scotland), and Southern Spawning Component (SSC, Gibraltar to southern Biscay); the existence of these spawning components still remains controversial Some studies on natal homing studies indicate the existence of structures within the spawning components (Nesbö et al, 2000; with mixing between them (Jansen and Gislason, 2013), although most of the studies failed to identify patterns (Jamieson and Smith, 1987;MacKenzie, 1990;Abaunza et al, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…Recent work comparing larval time series between the 1950s and 1970 s suggested that the spawning dynamics are more complicated and that the North Sea spawning stock should not be considered an isolated natal homing stock but instead is linked with the western spawning population (Jansen and Gislason, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Reasons for this have been attributed to possible decreases in foraging opportunities due to increased windinduced turbulence and decreasing zooplankton concentrations (Jansen, 2014). Another factor could have been the fishery in the northern North Sea during autumn and winter which targeted mackerel which could have otherwise contributed to spawning in the North Sea (Jansen and Gislason, 2013).…”
Section: Introductionmentioning
confidence: 99%